Comercio, tipo de cambio real y crecimiento económico - Enrique R. Casares (Estudios de Economía, 2007)
– We develop an endogenous growth model with three goods, exportable, importable and non-tradable. We study the response of the real exchange rate and of the economy growth rate to a decrease in the tariff rate. We show that trade liberalization must be followed by a depreciation of the real exchange rate. We deduce that the growth rate of the economy increases in the long run. We affirm that the Mexican economy did not follow this behavior in the period after the trade liberalization, so the result was a deficient economic growth.
Keywords: F43; O24; O41; 330; export sector; learning by doing; real exchange rate; growth